Brandon Rodrigues. A Shared History: Russian-Ukrainian Relations (1991 – 2014) - Rodrigues, Brandon (Young Scholars Grinchenko – Seton International Journal, 2022)
This work provides background for understanding the complex and close relationship between Russia and Ukraine from the fall of the Soviet Union in 1991 to the Russian annexation of Crimea in 2014. It covers topics such as Ukraine’s allocation of an inherited nuclear arsenal, the countries’ economic interdependence, the Orange Revolution, and Russia’s 2014 annexation of Crimea. This work aims to shed light on the complicated history of Russia and Ukraine following Russia’s full-scale invasion initiated on February 24th, 2022.